PERSPEKTIF “HUSTLE CULTURE” DALAM MENELAAH MOTIVASI DAN PRODUKTIVITAS PEKERJA - Rhoma Iskandar; Novi Rachmawati (Pusat Riset dan Inovasi Nasional, 2022)
Hustle culture has become a rising phenomenon in recent years. Especially among millennials who have such high enthusiasm and work ambition that questions arise about their motivation in doing hustle culture. In addition, can doing hustle culture at work achieve productivity? In this study, which discusses the relationship between hustle culture and work motivation and productivity, it turns out that the results are quite diverse. The relationship between hustle culture and work motivation and productivity is not entirely negative, there are positive impacts as well. So that hustle culture is not completely bad if it can be applied properly..